Traditional medical assistance using forward chaining Rule-Based System / Wan Mohamad Kamil Wan Salim - Wan Salim, Wan Mohamad Kamil (2020)
This project is done to develop a Traditional Medical Assistance Application using Forward Chaining Rule-Based System. Some people want to deal and cure their sickness and mild discomfort on their own and understand fully what they are having based on their symptoms. Many herbs and fruits are good to keep people healthy as they are rich in minerals and nutrients. Unfortunately they are not being exposed to these natural benefits and most people forgot the importance to understand this situation fully and make them afraid of any kind of symptom and decide to take the chemical medicine as an immediate solution which may cause various side effects in the long run. The objective of this project is to develop an application that provides folk remedies suggestion for common illness. The second objective of this project is to evaluate user acceptance testing of traditional medical assistance application. The software used to develop this project was the Android Studio. The method that is used for the developing of this project is Software Development Life Cycle (SDLC). The SDLC method includes the planning, analysis, designing, testing, implementing and development. This project helps user to get the best solution using common traditional remedies to cure their mild discomfort or illness based on their symptoms. Furthermore, a user acceptance test has been conducted on 30 respondents. The result shows that all respondents are satisfied with this application in term of how interesting, valuable and supportive the application is.